Indigenous plants used by the Otuo tribe of Owan East Local Government Area, Edo State, Nigeria - MacDonald Idu; Ovuakporie-Uvo Oghale; Ima-Osagie O. Sarah (AOSIS, 2017)
Background: Traditional medicine remains an integral part of the Otuo tribe in Owan East Local Government Area of Edo State. Aim: The study is aimed at documenting the ethnobotany of the Otuo tribe by evaluating the uses of plants found in the area, identifying the importance value (IV), fidelity level (FL) and principal taxonomic groups of the plants. Methods: Data were gathered following an oral interview of unlettered herbal practitioners. Literate men, women and young settlers in the community were cross-examined using a semi-structured questionnaire. Fifty respondents made up this study size. Data were collated to report botanical names, common and vernacular names of the species of plants surveyed. Information on the use, methods of preparation and plant part used was documented. The FL and IV were determined. Results: 101 plants belonging to 46 families were reported. The best-represented family was the Fabaceae with 11 species followed by the Euphorbiaceae with 6 species. Of the 101 plants, 80 plants have medicinal uses and 58 have other economic uses. Amongst the medicinal plants, Azadirachta indica had the highest FL and IV of 100 and 1.0, respectively, followed by Cymbopogon citratus with FL of 96; both plants are used to treat malaria. The major ailments treated with plants by the Otuo tribe include malaria, cataracts, rheumatism and dysentery, amongst others. Conclusion: The people of Otuo are rich in plant-based remedies. They devotedly practise local medicine use because it is cost-effective and efficient, thereby contributing greatly to the economic development of the area.